2021
DOI: 10.1111/trf.16338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body weight on hemoglobin increments in adult red blood cell transfusion

Abstract: Background Though weight is a major consideration when transfusing blood in pediatric patients, it is generally not considered when dosing transfusions in adults. We hypothesized that the change in hemoglobin (Hb) concentration is inversely proportional to body weight when transfusing red blood cells (RBC) in adults. Methods A total of 13,620 adult surgical patients at our institution were assessed in this retrospective cohort study (2009–2016). Patients were stratified based on total body weight (kg): 40–59.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[10][11][12] We acknowledge that the decision to stop transfusing blood is multifactorial in nature and certainly should not be based on laboratory values alone. Patient characteristics, comorbidities, and the nature of the disease process itself should all be taken into consideration, as multiple studies have demonstrated that these factors not only influence the efficacy of RBC transfusion, 32,33 but also impact clinical outcomes. 6,34 It is also important to note that the trend of laboratory values should be considered in conjunction with the absolute values, and that laboratory tests be ordered judiciously based on the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] We acknowledge that the decision to stop transfusing blood is multifactorial in nature and certainly should not be based on laboratory values alone. Patient characteristics, comorbidities, and the nature of the disease process itself should all be taken into consideration, as multiple studies have demonstrated that these factors not only influence the efficacy of RBC transfusion, 32,33 but also impact clinical outcomes. 6,34 It is also important to note that the trend of laboratory values should be considered in conjunction with the absolute values, and that laboratory tests be ordered judiciously based on the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transfusion effect, that is, Hb increase in patient's blood, varies significantly depending on several factors such as patient weight that correlates inversely to the Hb increase. [ 47 ] Moreover, we show here that the active agent of pRBCs, that is, Hb, varies substantially between pRBC units. This is even true for units of identical volume (Figure S2 , Supporting Information).…”
Section: Discussionmentioning
confidence: 74%
“…The actual ideal Hb incr per RBC unit depends on many factors, including patient blood volume, RBC unit Hb concentration, and actual RBC mass delivered. 5 Estimates of 24 h-Hb incr based on some of these key inputs has been previously reported. 6 The limitations and consequences of the mean ideal Hb incr of 1 g/dL/unit for each patient population is addressed further in the discussion section.…”
Section: Methodsmentioning
confidence: 99%
“…In this work 1 RBC unit was assumed to produce a mean ideal Hb incr of 1 g/dL. The actual ideal Hb incr per RBC unit depends on many factors, including patient blood volume, RBC unit Hb concentration, and actual RBC mass delivered 5 . Estimates of 24 h‐Hb incr based on some of these key inputs has been previously reported 6 .…”
Section: Methodsmentioning
confidence: 99%